Carbon dioxide insufflation and neurocognitive outcome of open heart surgery. (September 2015) - Ganguly, Gautam; Dixit, Vikas; Patrikar, Seema; Venkatraman, Ravishankar; Gorthi, Satya Prakash; Tiwari, Nikhil
Aim: Neurocognitive dysfunction continues to be the bane of open heart surgery despite vast improvements in surgical, anesthetic, and postoperative management. This observational cohort study was carried out to evaluate the efficacy of intraoperative CO2 insufflation by the field flooding technique in reducing postoperative neurocognitive dysfunction. Methods: Three hundred randomly selected patients undergoing open heart surgery were observed: 150 (group A) were exposed to CO2 insufflation, and the other 150 (group B) were not exposed to CO2 . Anesthetic, cardiopulmonary bypass, and myocardial protection techniques were standardized and similar in both groups. Neurocognitive function tests were performed preoperatively, 1 week postoperatively, and after 1 month. Results: The analysis revealed that neurocognitive dysfunction occurred in 8 of 150 patients in group A (incidence p1  = 0.053) and 27 of 150 in group B (incidence p2  = 0.18). The relative risk of neurocognitive dysfunction was 0.30 ( p  = 0.001, 95% confidence interval 0.14–0.63), implying that CO2 insufflation is protective against neurocognitive dysfunction. The risk difference was 0.13 ( p2 – p1 ); this implies that 13% of patients can be prevented from developing neurocognitive dysfunction if exposed to CO2 . Conclusion: This study confirms the known advantage of the relatively underutilized practice of CO2 insufflation. We recommend that CO2 insufflation be performed in all open heart surgery cases to bring down the incidence of neurocognitive dysfunction. This technique is simple to use without any major paraphernalia or additional cost.